Логіка добору дизайну клінічного дослідження з метою вивчення патогенезу цукрового діабету 2-го типу - Кіхтяк, О. П.; Нещерет, О. П. (Clinical Endocrinology and Endocrine Surgery, 2008)
For type 2 diabetes pathogenesis study purpose, cross-over study design possesses real advantage. Such approach gives opportunity to observe changes in pathogenesis following treatment. Given information (data) may be extrapolated in the concrete clinical case in order to give special recommendations regarding patient's pathogenesis picture of type 2 diabetes, so as for study general pattern and tendencies in the pathogenesis of this disease.